Third‐wave cognitive behaviour therapies for weight management: A systematic review and network meta‐analysis. (17th March 2020) - Lawlor, Emma R.; Islam, Nazrul; Bates, Sarah; Griffin, Simon J.; Hill, Andrew J.; Hughes, Carly A.; Sharp, Stephen J.; Ahern, Amy L.
Summary: This systematic review and network meta‐analysis synthesized evidence on the effects of third‐wave cognitive behaviour therapies (3wCBT) on body weight, and psychological and physical health outcomes in adults with overweight or obesity. Studies that included a 3wCBT for the purposes of weight management and measured weight or body mass index (BMI) pre‐intervention and ≥ 3 months post‐baseline were identified through database searches (MEDLINE, CINAHL, Embase, Cochrane database [CENTRAL], PsycINFO, AMED, ASSIA, and Web of Science). Thirty‐seven studies were eligible; 21 were randomized controlled trials (RCT) and included in the network meta‐analyses. Risk of bias was assessed using RoB2, and evidence quality was assessed using GRADE. Random‐effects pairwise meta‐analysis found moderate‐ to high‐quality evidence suggesting that 3wCBT had greater weight loss than standard behavioural treatment (SBT) at post‐intervention (standardized mean difference [SMD]: −0.09, 95% confidence interval [CI]: −0.22, 0.04; N = 19; I 2 = 32%), 12 months (SMD: −0.17, 95% CI: −0.36, 0.02; N = 5; I 2 = 33%), and 24 months (SMD: −0.21, 95% CI: −0.42, 0.00; N = 2; I 2 = 0%). Network meta‐analysis compared the relative effectiveness of different types of 3wCBT that were not tested in head‐to‐head trials up to 18 months. Acceptance and commitment therapy (ACT)‐based interventions had the most consistent evidence of effectiveness. Only ACT had RCT evidence of effectiveness beyond 18 months. Meta‐regression did not identify any specific intervention characteristics (dose, duration, delivery) that were associated with greater weight loss. Evidence supports the use of 3wCBT for weight management, specifically ACT. Larger trials with long‐term follow‐up are needed to identify who these interventions work for, their most effective components, and the most cost‐effective method of delivery.